Challenges Facing Families at the End of Life in Three Settings - Kehl, Karen A. (2009)
This study examined the challenges faced by family members at the end of life in different care settings and how those challenges compare across settings. A total of 30 participants, who had a family member die in inpatient hospice, a skilled nursing facility or a community support program were interviewed. Semi-structured interviews were recorded and transcribed. Text was coded using qualitative thematic analysis. Themes were determined by consensus. Twelve challenges were identified across care sites. Two themes emerged in all three settings: bearing witness and the experience of loss. The study findings contribute to our knowledge of family perceptions of care in different settings and raises awareness of the need for further research describing the experiences at the end of life in different settings and the importance of creating and testing interventions for both setting specific needs and universal issues.